Ultrasound‐ and Microwave‐Assisted Preparation of Lead‐Free Palladium Catalysts: Effects on the Kinetics of Diphenylacetylene Semi‐Hydrogenation. Issue 6 (16th February 2015) - Wu, Zhilin; Cherkasov, Nikolay; Cravotto, Giancarlo; Borretto, Emily; Ibhadon, Alex O.; Medlock, Jonathan; Bonrath, Werner
Abstract The effect of environmentally benign enabling technologies such as ultrasound and microwaves on the preparation of the lead‐free Pd catalyst has been studied. A one‐pot method of the catalyst preparation using ultrasound‐assisted dispersion of palladium acetate in the presence of the surfactant/capping agent and boehmite support produced the catalyst containing Pd nanoparticles and reduced the number of pores larger than 4 nm in the boehmite support. This catalyst demonstrated higher activity and selectivity. The comparison of kinetic parameters for diphenylacetylene hydrogenation showed that the catalyst obtained by using the one‐pot method was seven times as active as a commercial Lindlar catalyst and selectivity towards Z‐stilbene was high. Our work also illustrated that highly selective Pd/boehmite catalysts can be prepared through ultrasound‐assisted dispersion and microwave‐assisted reduction in water under hydrogen pressure without any surfactant.